UJI EFEKTIVITAS BEBERAPA JENIS ARANG AKTIF DAN NAUNGAN PADA TANAMAN SAWI PAHIT MENGGUNAKAN TANAH LAHAN BEKAS PENAMBANGAN EMAS - Uray Edi Suryadi; Dwi Raharjo; Elly Mustamir (Soil Science Department, Faculty of Agriculture, Tanjungpura University, 2016)
This study aims to determine the effect of shade and effectiveness of active charcoal derived from the raw material of palm shells and rice husks to absorb heavy metals Hg and Cu in bitter mustard / Chinese mustard plants (Brassicacea juncea). The mustard bitter in polybags with planting medium on the ex gold mining soils. The study design using split plot design, with the main plot factors are the type of the palm shells active charcoal (A1), and the rice husk active charcoal (A2). As a subplot factors are shade, that using shading net, consisting of 50% shade (P1), shade 60% (P2) and a shade 75% (P3). The results showed that the combination of 50% shade and active charcoal from shell palm oil can help the absorption of Cu and Hg at 0.92 ppm Cu and 5.11 ppb Hg in bitter mustard plant roots, as well as 0.42 ppm Cu and 2.96 ppb Hg on its leaves. The combination of 60% shade and activated charcoal from rice husk can help the absorption of Cu and Hg 0.67 ppm Cu and 4.11 ppb Hg in bitter mustard plant roots, as well as 0.23 ppm Cu and 4.09 ppb Hg on its leaves. Whereas 70% shade combinations and active charcoal from rice husk can help the absorption of Cu and Hg 0.57 ppm Cu and 4.89 ppb Hg in bitter mustard plant roots, as well as 0.13 ppm Cu and 4.75 ppb Hg on its leaves.Keywords : active charcoal, bitter mustard, Cu, ex PETI soil, Hg, shade